METHODS AND TECHNIQUES OF PERCUTANEOUS EXTERNAL FIXATION IN PELVIC FRACTURES - Pavlin Apostolov; Martin Burnev; Petar Milkov (Peytchinski Publishing, 2011)
The authors make a review and present their experience with the use of percutaneous external fixation techniques in pelvic fractures: (1) Transiliac placement (classic method - through the wings of the iliac bone, behind anterior superior iliac spine); (2) Sub-Iliac Crest technique (beneath and along the length of iliac crests); (3) Supra-acetabular Method (Frontal, antero-inferior). They review as well different variants of half-pin placement techniques and analyze the final results of external pelvic fixation study including 65 patients for 10-year period. The authors recommend more frequently usage of antero-inferior technique (supra-acetabular). According to them, this method exceeds the other techniques by many criteria.